2001
DOI: 10.1128/iai.69.9.5430-5439.2001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Availability of Oxygen Accentuate Differences in Capsular Polysaccharide Expression by Phenotypic Variants and Clinical Isolates of Streptococcus pneumoniae

Abstract: Most isolates ofIn patients with invasive infection, paired isolates from the same patient were shown to have predominately a T colony phenotype without phosphotyrosine on CpsD when cultured from the nasopharynx, and an O phenotype that phosphorylates CpsD in response to oxygen when cultured from the blood. Differences in the availability of oxygen, therefore, may be a key factor in allowing for the selection of distinct phenotypes in these two host environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
94
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(113 citation statements)
references
References 40 publications
16
94
2
1
Order By: Relevance
“…T colonies appear smaller in size, concave (umbilicated) and transparent in the center. The opaque colony is larger, more uniformly whitish throughout and with a domed center as previously described [14]. The edge of the colony is slightly irregular in the T variant, but smoother in the opaque variant.…”
Section: Pneumococcal Phase Variantsmentioning
confidence: 51%
“…T colonies appear smaller in size, concave (umbilicated) and transparent in the center. The opaque colony is larger, more uniformly whitish throughout and with a domed center as previously described [14]. The edge of the colony is slightly irregular in the T variant, but smoother in the opaque variant.…”
Section: Pneumococcal Phase Variantsmentioning
confidence: 51%
“…However, after invasion there is a predominance of the opaque phenotype (Weiser et al, 2001) and anaerobic conditions cause an increase in the amount of capsule in opaque variants. As stated by Weiser et al (2001), the bacteria would be exposed to the highest ambient oxygen levels when on the airway surface, but the oxygen tension encountered would be much lower during pneumonia, in blood or in the middle ear. It would be interesting to determine in further studies whether in opaque clinical isolates there is a change in the transcription of cpsA under anaerobic conditions and whether this differs between serotypes with high and low invasive potential.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in animal models have shown that transparent variants are released when nasal tissues are washed with physiological salt solutions, while the majority of S. pneumoniae isolates recovered from previously washed homogenized nasal tissue, from blood specimens, or from lung aspirates were in the opaque phase (1,12). In chinchillas pretreated with live influenza virus, inoculation with opaque pneumococci caused more severe middle ear infections than did inoculation with transparent pneumococci (10).…”
mentioning
confidence: 99%
“…However, the phase shifts have never been clearly demonstrated with human samples. A study in 2001 examined 19 "minimally passaged" paired nasal and blood isolates, but no statistical association was observed between the phase and body isolation site (P ϭ 0.51) (12). The present study was designed to investigate the morphological phase of pneumococci by plating them on transparent agar immediately upon their isolation from the nasopharynx and middle ear of children with AOM.…”
mentioning
confidence: 99%